Combustion mechanism and product characteristics of 2, 3, 3, 3-tetrafluoropropene as an environmentally friendly working fluid for organic Rankine cycle. (1st April 2023) - Chen, Yubo; Yang, Zhao; Lv, Zijian; Zhang, Yong; Li, Jie; Fei, Teng
Abstract: Organic Rankine cycle (ORC) is an effective way to utilize low-grade energy. 2, 3, 3, 3-tetrafluoropropene (R1234yf) has attracted extensive attention due to its good environmental protection performance and is considered as an alternative working fluid in ORC. However, its thermodynamic, environmental and safety characteristics need to be fully considered. In this paper, the combustion mechanism and product characteristics of R1234yf were investigated by ReaxFF molecular dynamics simulations. The reaction temperature and equivalence ratio have important effects on the combustion of R1234yf. The early stage of the combustion process is mainly the unimolecular decomposition reaction of R1234yf, and then O2 participates in the reaction, the consumption rate of R1234yf increases rapidly, the radicals O, H, OH, CF3, CF2, and CFO play important roles in the combustion reaction. The main combustion products include CO, CO2, HF, and COF2 . In addition, the combustion product concentration and yield of R1234yf were tested by an improved method. The results showed that the change law of combustion product yield with equivalence ratio was in good agreement with the simulation results, and the risk of high CO and HF concentrations still exists. The research results have practical significance for the safe application of R1234yf in ORC system. Highlights: The combustion mechanism of R1234yf was studied by ReaxFF-MD simulations. The reaction conditions have important effects on the combustion of R1234yf. The concentration and yield of combustion products were measured and analyzed. The variation law of combustion products of R1234yf was obtained.